2010
DOI: 10.1016/j.bone.2010.03.021
|View full text |Cite
|
Sign up to set email alerts
|

FGFR3 signaling induces a reversible senescence phenotype in chondrocytes similar to oncogene-induced premature senescence

Abstract: Oncogenic activation of the RAS-ERK MAP kinase signaling pathway can lead to uncontrolled proliferation but can also result in apoptosis or premature cellular senescence, both regarded as natural protective barriers to cell immortalization and transformation. In FGFR3-related skeletal dyplasias, oncogenic mutations in the FGFR3 receptor tyrosine kinase cause profound inhibition of cartilage growth resulting in severe dwarfism, although many of the precise mechanisms of FGFR3 action remain unclear. Mutated FGFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 47 publications
3
28
0
Order By: Relevance
“…Ectopic expression of the FGFR3 mutants results in their activation via spontaneous dimerization, with the activating potential of the given mutation easily appreciated by the level of ERK phosphorylation (Fig. 6A) [12]. We also demonstrate the Thr1572 phosphorylation of LRP6, which took place in cells expressing highly activating FGFR3 mutants R248C and K650E (Fig.…”
Section: Resultssupporting
confidence: 51%
“…Ectopic expression of the FGFR3 mutants results in their activation via spontaneous dimerization, with the activating potential of the given mutation easily appreciated by the level of ERK phosphorylation (Fig. 6A) [12]. We also demonstrate the Thr1572 phosphorylation of LRP6, which took place in cells expressing highly activating FGFR3 mutants R248C and K650E (Fig.…”
Section: Resultssupporting
confidence: 51%
“…As mentioned above, a positive correlation between RAS expression and A-type lamin expression was found in human seminomas [ 16 ]. In parallel to these results, a recent study showed that in osteoblast differentiation by FGF3 activation, leading to RAS and ERK activation, expression of lamin A/C is increased [ 45 ]. As for SCLC, the mechanism by which increased LMNA expression is achieved upon RAS activation is unclear so far.…”
Section: Lung Cancer Cell Linesmentioning
confidence: 54%
“…It is known that v-Ha-RAS can cause proliferation in some cells and senescence induction in other cells. In the SCLC cell line NCI-H249 it seems that v-Ha-RAS expression leads to a cell phenotype with both increased growth and increased levels of differentiation [ 47 ], accompanied by an increase in lamin A/C expression [ 43 ], while, as mentioned above, in osteoblasts, enhanced normal RAS expression causes differentiation and senescence [ 45 ]. …”
Section: Lung Cancer Cell Linesmentioning
confidence: 99%
“…Sustained activation of ERK can induce cell senescence. A study [82] using rat chondrosarcoma cells demonstrated that sustained ERK activation mediated by FGFR3 promoted the expression of the senescent phenotype markers. Extracellular ROS could also contribute to inhibition of the Akt pathway through oxidized low-density lipoprotein (LDL).…”
Section: Chondrocyte Changesmentioning
confidence: 99%